A new genus and species of cavernicolous Pomatiopsidae (Mollusca, Caenogastropoda) in Bahia, Brazil - Simone, Luiz Ricardo L. (Papéis Avulsos de Zoologia, 2012)
Spiripockia punctatais a new genus and species of Pomatiopsidae found in a cave from Serra Ramalho, SW Bahia, Brazil. The taxon is troglobiont (restricted to subterranean realm), and is characterized by the shell weakly elongated, fragile, translucent, normally sculptured by pustules with periostracum hair on tip of pustules; peristome highly expanded; umbilicus opened; radular rachidian with 6 apical and 3 pairs of lateral cusps; osphradium short, arched; gill filaments with rounded tip; prostate flattened, with vas deferens inserting subterminally; penis duct narrow and weakly sinuous; pallial oviduct simple anteriorly, possessing convoluted bypass connecting base of bulged portion of transition between visceral and pallial oviducts with base of seminal receptacle; spermathecal duct complete, originated from albumen gland. The description of this endemic species may raise protective environmental actions to that cave and to the Serra Ramalho Karst area.